CHANGES IN ECONOMIC STRUCTURE OF EAST JAVA AND THE POLICY OF EAST JAVA PROVINCIAL GOVERMENT - Nian Riawati (UPT Penerbitan Universitas Jember)
The decline in agricultural sector contribution to the GDP of East Java year period 2012-2014 evidence of a shift in the economic structure of East Java of the tradable sector / base in the non-tradable sector. Several previous studies mention their negative impact on the tradable sector shift in the non-tradable sector. Whereas, shifting the economic structure will increase poverty, unemployment and raising the Gini ratio. This study analyzes the policy taken by the Government of East Java Province, in anticipation of a shift in the economic structure, so not many have a negative impact on the increase in poverty and growing unemployment. This type of research is descriptive qualitative approach. The research data is secondary data as well as the results of previous research. Research explains some eastern Java provincial government policies that do them, First strengthening tradable sectors through policy development of Micro, Small and Medium Enterprises (SMEs). Second, the policy on the education sector through the development of vocational schools (SMK) Third, policies on finance sector. The conclusion of this study stated that the East Java Provincial Government policy succeeded in anticipating shifting economic structure so not much give a negative impact to the decline in poverty and unemployment.